The Impact Of Inquiry-Based Learning On K-12 Students’ Motivation And Science Literacy: A Systematic Literature Review - Diego Stefvannof; Winarto Winarto; Imroatun Nadifah; Melati Latifah (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This systematic literature review (SLR) explores the impact of inquiry-based learning (IBL) on K–12 students’ learning motivation and science literacy. A total of 20 empirical studies published between 2018 until 2025 were selected using PRISMA 2020 guidelines from Scopus, SpringerLink, and Elsevier databases. The studies employed various inquiry-based learning models (guided, open, and socio-scientific), educational levels, and instructional media. The findings show that inquiry-based learning consistently enhances students’ intrinsic motivation by fostering autonomy, engagement, and contextual learning. Simultaneously, inquiry-based learning improves science literacy through inquiry cycles involving observation, hypothesis testing, experimentation, and reasoning. Guided inquiry appears to be the most effective form, particularly at primary and lower secondary levels, while hybrid models like SSIBL and IB-NOSA enhance students’ argumentation and scientific thinking. However, the effectiveness of inquiry-based learning is influenced by teacher readiness, duration of intervention, and technological support. This review reinforces the pedagogical relevance of inquiry-based learning in promoting 21st-century competencies and suggests its integration into curriculum design, teacher training, and science education policies